Dielectric and Thermal Behavior of Polystyrene/Sr2TiMnO6 (STMO) Composites. Issue 2 (3rd April 2021) - Ashokbabu, Angalakurthy; Thomas, Paramanandam
Abstract : Materials with high dielectric permittivity are in demand due to their potential applications in microelectronics, capacitors and related fields. Polymer/ceramic composites, due to their improved properties, can be studied to meet this demand. In this work, high permittivity double perovskite Sr2 TiMnO6 (STMO) ceramics were synthesized by solid state reaction route and polystyrene (PS) composite thick films (∼200 μm) with up to 50 vol% loading of STMO were prepared by solution casting technique. The composite films were characterized using X-ray diffraction and Fourier transform infra-red spectroscopy for their structural properties. Microstructure of the composites was examined using scanning electron microscopy. Thermal behavior was studied using differential scanning calorimetry and thermo-gravimetric analysis. Dielectric properties, such as permittivity, loss and AC conductivity were measured using a dielectric impedance analyzer. Permittivity and dielectric loss of the base polymer were found to increase with the addition of STMO. Glass transition for composites shifted to higher temperature than that of pure PS. The composites exhibited enhanced thermal stability and these composite films can be explored as dielectric materials for capacitor applications. GRAPHICAL ABSTRACT: UF0001